2022
DOI: 10.3390/ijerph191711074
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Ochratoxin A from Rice Consumption in Lebanon and United Arab Emirates: A Comparative Study

Abstract: Our study aims to evaluate the ochratoxin A (OTA) in rice marketed in Lebanon and the United Arab Emirates (UAE), and to determine the exposure to OTA from rice consumption. All brands available in the market were collected twice (total number of collected samples: 105 and 127 in Lebanon and the UAE, respectively). Using ELISA, the OTA in 56 (53%) samples in Lebanon and 73 (58%) samples in the UAE were above the limit of quantification (0.8 μg/kg). The average concentrations of the positive samples ± standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Only one sample (1%) in Lebanon had a level at the borderline of the European Union (EU) limit, and two samples (1.6%) in the UAE had a level above the EU limit (5 μg/kg). In our study, no significant difference was found between SKUs from Lebanon versus other countries in terms of OTA, which goes in line with the findings of 10 . In addition, average concentration of OTA in our study was 1.2 μg/kg, which is close similar to the one reported by 10 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Only one sample (1%) in Lebanon had a level at the borderline of the European Union (EU) limit, and two samples (1.6%) in the UAE had a level above the EU limit (5 μg/kg). In our study, no significant difference was found between SKUs from Lebanon versus other countries in terms of OTA, which goes in line with the findings of 10 . In addition, average concentration of OTA in our study was 1.2 μg/kg, which is close similar to the one reported by 10 .…”
Section: Resultssupporting
confidence: 91%
“…In our study, no significant difference was found between SKUs from Lebanon versus other countries in terms of OTA, which goes in line with the findings of 10 . In addition, average concentration of OTA in our study was 1.2 μg/kg, which is close similar to the one reported by 10 .…”
Section: Resultssupporting
confidence: 91%
“…In addition, food safety in Lebanon has been at stake in the last decade due to poor control from the inspection authorities [ 36 ]. In fact, previous studies conducted in Lebanon mainly investigated the presence of mycotoxins in herbs, spices, rice, wheat, and infant formulas, among others, but not including tea, which is a frequently consumed beverage in Lebanon [ 37 , 38 , 39 , 40 , 41 , 42 ]. Compared to the aforementioned studies from Lebanon, the prevalence of mycotoxins in tea in this study is lower than what was reported in other food products (human milk, dairy products, rice, and spices).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are more than 300 discovered mycotoxins, 30 of them are the most significant and commonly detected in food, including aflatoxins (AFs), ochratoxins (OTs), fumonisins (FBs), patulin, zearalenone (ZEN) and trichothecenes. These mycotoxins can naturally contaminate feed and food products, such as nuts, cereals, fruits, vegetables, spices, herbs and coffee beans, and can be detected in animal products, such as meat, milk and eggs, if the animals have consumed contaminated feed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%